Citizenship and human security in Iraq after 2003 .. Dimensions and security implications (قضايا سياسية, 2023)
Oppressed nations tend to have bad manners" this psychology quote defines one of the negative results of deprive and oppression that may affect any community. The Iraqi community for example has suffered for a long period of time from force rolling then foreign invasion and security threat represented in a vast wave of terrorism that across the country in addition to the a deteriorating economic situation that led to an increase in unemployment rates through a relatively long transitioning era for one party system to multiple party system which has led to further delay to complete people's required and desired corrections that can improve his living reality. The reaction of a large segment of the oppressed people was negative towards their state through the decline in the concept of citizenship as a result of the shrinking margin of trust between the citizen in one hand and the successive governments in managing state affairs on the other hand. Thus, Iraq witnessed negative phenomena, such as the spread of drug addiction, organized crime, and involvement in the ranks of terrorist organization or legitimate demand demonstrations, some of which included abnormal cases of violence and assaults on public and private property (i.e. non-good female or male citizen), or searching for an alternative to the state, by giving priority to sub – affiliations such as national, sectarian, tribal, partisan, and foreign affiliations over belonging to the homeland. (i.e., the decline in the level of national belonging), with the recording of cases of external migration, whether to search for safety or to earn a living, i.e. the migration of labor, human energies, and qualified scientific cadres, which collectively negatively affected the strengthening of Iraqi national security.